Dyslexics "knowing how" to challenge Lexism - Barden, Owen (Routledge, 2017)
In this chapter we argue that historic conceptual confusion between ‘knowing how’ and ‘knowing that’ (Ryle, 1949) has helped construct dyslexia as a literacy difficulty. Normative literacy practices, which we call Lexism, have compounded the difficulty. We suggest that social media contribute to changing conceptions of ‘what counts’ as literacy and promote reconsideration of the deficit discourse in relation to dyslexia and literacy.
Disability and Social Media.
Keywords: Digital Humanities; Inclusive Society; Computer Education/Literacy; Computers & Education; E-Learning; Inclusive Education; Information technology in education; Innovation in learning; Literacy; Participatory Research Methods; Specific learning difficulties; Education